Surgical Outcome of Cranioplasty between Frozen Autologous Bone Flap versus Synthetic Acrylic Cement Flap. (Bangladesh Journal of Neurosurgery, 2026)
Cranioplasty (CPL) is a surgical procedure performed to restore a defect on the cranial vault after a previous  decompressive craniectomy made for traumatic brain injury, ischemic or hemorrhagic disease or even after the  removal of cranial tumors. Although apparently it may resemble an easy and routine surgical procedure, cranioplasty  has several complications. The most frequently reported complications are infections, autologous bone flap  resorption, cerebrospinal fluid leak, subdural effusion, seizures, syndrome of the trephined, hematomas & poor  cosmetic result. The objectives of cranioplasty are (1) to restore the earlier contour of skull bone (2) to protect the  underlying brain and (3) to diminish the complications of a craniectomy. Readily available and traditionally used frozen  autologous bone graft for primary reconstruction is associated with complications. Recent reports suggest that  synthetic acrylic cement flap might have better surgical outcome.  Aims: The objective of the study was to compare the surgical outcome of cranioplasty between frozen autologous  bone flap and synthetic acrylic cement flap.  Methods: This cross-sectional analytical study was carried out in the department of Neurosurgery, Dhaka Medical  College and Hospital, Dhaka. Total 70 samples were taken and allocated equally into two group- Group-A (35 patients  with frozen autologous bone flap) and Group-B (35 patients with synthetic acrylic cement flap). The data regarding  socio- demographic, clinical, bio-chemical, imaging and surgical outcome were recorded processed and analyzed with  the Statistical Package for Social Science (SPSS) version-22.0 and Microsoft Excel. Quantitative data expressed as  mean standard deviation and qualitative data as frequency and percentage. Comparison was done by tabulation and  graphical presentation in the form of tables, pie chart, graphs, bar diagrams, histogram & charts etc.  Results: Study demonstrates that maximum number of patients (e.g., 31.4%) were between 31-40 years’ age group.  Mean age of the patient was 32.37 ± 11.50 years in group-A and 33.31 ± 16.86 years in group-B. Male and female  ratio was 4.8:1. Although recovery rate was predominant in group-B patients, but the difference was non-significant (p  = 0.176). Study shows that 20.0% of the patients in group-A developed complication after surgery, whereas compilation  rate was 8.5% in group-B patients. Study revealed that superficial incisional SSI was 11.4% patients in group-A &  5.7% in group-B, deep incisional SSI was 2.9% patients in group-A & none of case in group-B, cerebrospinal fluid leak  was 5.7% in group-A & 2.9% in group-B. Bone resorption was 2.9% in group A & none of case in group B.  Conclusions: This study revealed that synthetic acrylic cement flap cranioplasty is associated with better surgical  outcome than frozen autologous bone flap.  Keywords: CPL(Cranioplasty), PMMA(Polymethylmethacrylate), BFR (Bone flap resorption), GCS (Glasgow coma  scale), GOS (Glasgow outcome score), DC (Decompressive craniectomy) Bang. J Neurosurgery 2024; 14(1): 54-59